2017
DOI: 10.20943/01201701.1524
|View full text |Cite
|
Sign up to set email alerts
|

Improved Decoding of linear Block Codes using compact Genetic Algorithms with larger tournament size

Abstract: Soft-decision decoding is a very important NP-hard problem for developers of communication systems. In this work we propose two new dual domain soft decision decoders that use compact Genetic Algorithm (cGA) with larger tournament size: the first algorithm investigates tournament selection with larger size using mutation, and the second employs higher selection pressure with randomly generated individuals. The obtained results are compared to known previous works and show the effectiveness of using larger tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…There are other methods that use non-algebraic techniques, such as genetic algorithms that belong to evolutionary techniques [18]- [19]. We have also found a work that uses local search to find errors [20]- [21].…”
Section: Related Workmentioning
confidence: 92%
“…There are other methods that use non-algebraic techniques, such as genetic algorithms that belong to evolutionary techniques [18]- [19]. We have also found a work that uses local search to find errors [20]- [21].…”
Section: Related Workmentioning
confidence: 92%
“…У [8] даний підхід отримав подальший розвиток шляхом застосування компактного генетичного алгоритму зі збільшеним розміром турніру при здійсненні м'якого декодування блокових кодів. Проведений аналіз обчислювальної складності розроблених методів декодування показав, що представлені модифікації не вносять суттєвих обмежень та значно підвищують ефективність декодування для обраних блокових кодів.…”
Section: аналіз літературних даних і постановка проблемиunclassified
“…Article [22] presented the methods for decoding linear block codes in the binary space based on the compact genetic algorithm with an increased size of the tournament The work proposed different approaches to increasing the size of the tournament and determined the influence of the parameters of the selected genetic algorithm on the quality of decoding of algebraic block codes. It was shown that the proposed decoding methods provide high enough gain from encoding and are characterized by a reduced computational complexity.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%